2005
DOI: 10.1177/0032885505279467
|View full text |Cite
|
Sign up to set email alerts
|

Parole and Revocation: Perspectives of Young Adult Offenders

Abstract: This article presents the findings of an exploratory study of parole release and parole failure as seen through the eyes of inmates who have been returned to prison following parole revocation. The small sample of revoked inmates was limited to parolees of a young adult offender (YAO) program. The YAO program was designed for young men who were (a) under the age of 18 at the time of conviction, (b) waived to the adult system, and (c) sentenced to a term of imprisonment in an adult prison. This research project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 5 publications
(4 reference statements)
4
18
0
Order By: Relevance
“…For example, research reveals that prisoners taking college classes were motivated to become positive role models for their families (Heiser, 2007;Winterfield, 2009), and prisoners enjoyed taking college classes in prison because it helps them have a positive outlook while in prison (Bhatti, 2010;Heiser, 2007;Winterfield, 2009). In addition, our results affirm the importance of becoming a role model and actually taking college classes as had been revealed in the few previous qualitative studies of parolees (i.e., Hall, 2003;Hanrahan et al, 2005;Richards, 1992;Richards et al, 2004).…”
Section: Summary Connections and Conclusionsupporting
confidence: 89%
“…For example, research reveals that prisoners taking college classes were motivated to become positive role models for their families (Heiser, 2007;Winterfield, 2009), and prisoners enjoyed taking college classes in prison because it helps them have a positive outlook while in prison (Bhatti, 2010;Heiser, 2007;Winterfield, 2009). In addition, our results affirm the importance of becoming a role model and actually taking college classes as had been revealed in the few previous qualitative studies of parolees (i.e., Hall, 2003;Hanrahan et al, 2005;Richards, 1992;Richards et al, 2004).…”
Section: Summary Connections and Conclusionsupporting
confidence: 89%
“…The transition to living situations with caregivers was exacerbated in that most (six of nine of individuals in the sample) had been living with delinquent peers and engaging in illegal activities prior to incarceration, to both support and avoid scrutiny from family members and caregivers. Hanrahan, Gibbs, and Zimmerman (2005) reported that families often did what they could but that limited resources prevented them from providing meaningful assistance in many cases. Still, family ties were identified as critical.…”
Section: The Burden Of High Expectationsmentioning
confidence: 99%
“…Hanrahan et al (2005) found that male offenders spoke about their experience of being released from a juvenile facility in a similar manner. Specifically, these men described a desire to interact with family members when released.…”
Section: Repetition Of Oldmentioning
confidence: 94%